2019
DOI: 10.1039/c9ra08634j
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial strain modulated the electronic structure of hydrogenated 2D tetragonal silicene

Abstract: Hydrogenation can open the band gap of 2D tetragonal silicene, α-SiH is semiconductors with a direct band gap of 2.436 eV whereas β-SiH is indirect band gap of 2.286 eV. The band gap of α-SiH, β-SiH and γ-SiH can be modulated via biaxial strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Similar to graphene, silicene can also form haeckelite structures. Typically Si haeckelites have higher formation energies than carbon haeckelites, but they can be stabilized either via dumbbells ,, or hydrogenation . SiH–X and SiH–XII are examples of such structures (see Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to graphene, silicene can also form haeckelite structures. Typically Si haeckelites have higher formation energies than carbon haeckelites, but they can be stabilized either via dumbbells ,, or hydrogenation . SiH–X and SiH–XII are examples of such structures (see Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Typically Si haeckelites have higher formation energies than carbon haeckelites, but they can be stabilized either via dumbbells 46,55,56 or hydrogenation. 57 SiH− X and SiH−XII are examples of such structures (see Figure 10). Although they are higher in energy than silicane by about 0.05 eV/atom, the stabilizing effect of H allows not to rule out the possibility to synthesize these interesting 2D phases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Defects, impurities and environmental stability may alter the results of this work, which are based on pure TS. Recent research has demonstrated that hydrogenated TS contains a band gap in its band structure that is also tunable by biaxial strain [67]. According to [68], vacancies, ad-atom addition and oxidation result in a small to high bandgap for hexagonal silicene.…”
Section: Electrical Transportmentioning
confidence: 99%
“…α‐SiH showed a direct band gap of 2.436 eV while β‐SiH has 2.286 eV indirect band gap. [ 17 ] Nguyen et al investigated the geometric, electronic, and magnetic properties of double‐sided and single‐sided (fluorine F, chlorine Cl, bromine Br, iodine I, and astatine At) adsorbed silicene systems. The systems of least adsorption ratio (i.e., Halogen:Silicon) have gained the highest binding energies (−2.207 to −5.458 eV) with buckling heights (0.760 to 0.910 Å) for double‐sided halogen adsorption.…”
Section: Introductionmentioning
confidence: 99%